NLRP12 downregulates the Wnt/β-catenin pathway via interaction with STK38 to suppress colorectal cancer - Shahanshah Khan; Youn-Tae Kwak; Lan Peng; Shuiqing Hu; Brandi L. Cantarel; Cheryl M. Lewis; Yunpeng Gao; Ram S. Mani; Thirumala-Devi Kanneganti; Hasan Zaki (The Journal of Clinical Investigation, 2023)
Colorectal cancer (CRC) at advanced stages is rarely curable, underscoring the importance of exploring the mechanism of CRC progression and invasion. NOD-like receptor family member NLRP12 was shown to suppress colorectal tumorigenesis, but the precise mechanism was unknown. Here, we demonstrate that invasive adenocarcinoma development in Nlrp12-deficient mice is associated with elevated expression of genes involved in proliferation, matrix degradation, and epithelial-mesenchymal transition. Signaling pathway analysis revealed higher activation of the Wnt/β-catenin pathway, but not NF-κB and MAPK pathways, in the Nlrp12-deficient tumors. Using Nlrp12–conditional knockout mice, we revealed that NLRP12 downregulates β-catenin activation in intestinal epithelial cells, thereby suppressing colorectal tumorigenesis. Consistent with this, Nlrp12-deficient intestinal organoids and CRC cells showed increased proliferation, accompanied by higher activation of β-catenin in vitro. With proteomic studies, we identified STK38 as an interacting partner of NLRP12 involved in the inhibition of phosphorylation of GSK3β, leading to the degradation of β-catenin. Consistently, the expression of NLRP12 was significantly reduced, while p-GSK3β and β-catenin were upregulated in mouse and human colorectal tumor tissues. In summary, NLRP12 is a potent negative regulator of the Wnt/β-catenin pathway, and the NLRP12/STK38/GSK3β signaling axis could be a promising therapeutic target for CRC.